2013
DOI: 10.1134/s0362119713040075
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the low- and high-frequency oscillations of the EEG α-band in the intervals between meaningful visual stimuli

Abstract: Differences in induced synchronization of the high frequency and low frequency α rhythm between the group of subjects in whom switching and updating of the cognitive set are not accompanied by errors in recognition of facial expression (the high plastic set) and the subjects making errors were revealed in healthy adults (n = 35) using the model set to the perception of an angry face. In the former, the well marked synchronization of the high frequency α rhythm occurs in pauses between the trials. This phenom e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Thus, alpha-band activity was lower in prefrontal regions during atVNS stimulation and lower when there was also a decline in task performance. Alpha-band activity is linked to attentional processing and cognitive control mechanisms ( Lu et al, 2017 ; Clements et al, 2021 ) in that they are relevant for the suppression of irrelevant/interfering information ( von Stein et al, 2000 ; Palva and Palva, 2007 ; Klimesch, 2012 ; Kostandov and Cheremushkin, 2013 ; Suzuki et al, 2018 ). Mainly prefrontal regions are critically involved in such top-down control processes ( Miller and Cohen, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, alpha-band activity was lower in prefrontal regions during atVNS stimulation and lower when there was also a decline in task performance. Alpha-band activity is linked to attentional processing and cognitive control mechanisms ( Lu et al, 2017 ; Clements et al, 2021 ) in that they are relevant for the suppression of irrelevant/interfering information ( von Stein et al, 2000 ; Palva and Palva, 2007 ; Klimesch, 2012 ; Kostandov and Cheremushkin, 2013 ; Suzuki et al, 2018 ). Mainly prefrontal regions are critically involved in such top-down control processes ( Miller and Cohen, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, especially during conflict monitoring, adjustments in attentional selection processes play an essential role ( Reynolds and Chelazzi, 2004 ; Gazzaley and Nobre, 2012 ). Interestingly, alpha-band activity is linked to attentional processing and cognitive control mechanisms ( Lu et al, 2017 ; Clements et al, 2021 ) in that they are relevant for the suppression of irrelevant/interfering information ( von Stein et al, 2000 ; Palva and Palva, 2007 ; Klimesch, 2012 ; Kostandov and Cheremushkin, 2013 ; Suzuki et al, 2018 ). Studies have shown that alpha activity modulates behavioral conflicts in congruency tasks ( Tang et al, 2013 ; Wu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…With a pause of 16 sec: 1) the group of subjects not making any errors during switching of the acting stimuli continued to exist, though it became smaller, though overall the number of erroneous recognitions did not increase significantly; 2) members of the "no errors" group showed greater synchronization during the interstimulus period, this affecting both the low-frequency and the high-frequency components of the α rhythm, as compared with subjects in whom stimulus switching led to erroneous recognition of new stimuli in the forms of perseverative and contrast illusions. Synchronization of the α rhythm, especially its highfrequency subrange, has previously been observed in subjects not making errors in analogous experiments with an interKostandov, Cheremushkin, Yakovenko, and Petrenko 160 stimulus interval of 8 sec [2,3]. In all these experiments, the loading on working memory consisted only of an increase in the time interval during which the subject had to retain the result of the comparative evaluation of the emotional expressions of two faces in memory and press a button and provide a verbal report of their decision in response to the trigger stimulus.…”
Section: Discussionmentioning
confidence: 83%
“…1 show that at the set formation stage (when all subjects correctly recognized the difference in the emotional facial expressions in all 15 trials), a desynchronization reaction was seen during the first second after presentation of the target stimulus (S1), this affecting both the low-frequency and high-frequency components of the α rhythm to the same extents, in the "no errors" group of subjects and in groups with larger numbers of errors. This reaction was weaker in subjects with relatively small numbers of errors (1)(2)(3)(4)(5).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation